Cascaded H-bridge 7-level inverter application for air exhaust fan drive control of Thu Thiem road tunnel - Thu Anh, An Thi Hoai; Cuong, Tran Hung; Khoi, Tran Van (Institute of Advanced Engineering and Science, 2025)
The Thu Thiem road tunnel in Vietnam is crucial in reducing traffic congestion and ensuring the safety of those passing through, thanks to its ventilation system that generates clean air. This fresh air production is primarily supported by two exhaust fans at both ends of the tunnel in the eastern and western towers. However, the fans have a power capacity of several hundred kW and operate at kilovolt-level voltage, which is unsuitable for conventional inverters. Therefore, this paper proposes a 7-level inverter to feed the exhaust fan drive motor. The 7-level inverter improves the output voltage quality, and the output current and voltage have reduced the harmonic distortion significantly. The outstanding advantages of this inverter are verified through MATLAB/Simulink simulation software compared to a 3-level inverter.